2021
DOI: 10.1186/s13071-021-04924-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and population differentiation in Hepatozoon canis (Apicomplexa: Hepatozoidae) reveal expansion and gene flow in world populations

Abstract: Background Hepatozoon canis is a protozoan transmitted to dogs and other wild carnivores by the ingestion of ticks containing mature oocysts and is considered the principal cause of canine hepatozoonosis in the world. Here, we examined ribosomal RNA 18S gene sequence variation to determine the genetic differences and phylogeographic diversity of H. canis from various geographical areas around the world. Methods We used 550 publicly available sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…These results were much lower than that of H . canis ( 27 ), but similar to Plasmodium knowlesi ( 55 ) and Plasmodium vivax ( 56 ). Haplotype analysis indicated that the genetic diversity was observed with high haplotype diversity in Asian countries except for Bangladesh and India.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These results were much lower than that of H . canis ( 27 ), but similar to Plasmodium knowlesi ( 55 ) and Plasmodium vivax ( 56 ). Haplotype analysis indicated that the genetic diversity was observed with high haplotype diversity in Asian countries except for Bangladesh and India.…”
Section: Discussionmentioning
confidence: 98%
“…The average haplotype diversity of 0.474 and 0.473 were in Asia and the three continents, respectively, which was lower in comparison with other protozoa such as H . canis ( 27 ) and P. knowlesi ( 55 ). Population size is an essential factor in affecting the genetic diversity, therefore, lower haplotype diversity seemed to correlate with a small effective population size in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations